2015
DOI: 10.1016/j.actamat.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness testing of nanocrystalline alumina and fused quartz using chevron-notched microbeams

Abstract: We show that chevron-notched samples offer an attractive approach to the measurement of fracture toughness in micron-scale samples of brittle materials and use the method to characterize quartz and nanocrystalline alumina. Focused ion beam milling is used to carve bend bars of rectangular cross-section a few micrometres wide and containing a notch with a triangular ligament. Load-controlled testing is conducted using a nanoindentation apparatus. If the notch is appropriately machined, cracks nucleate and propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 66 publications
(90 reference statements)
2
53
0
2
Order By: Relevance
“…However, the methodology entails a large experimental scatter owing to the uncertainty in the determination of the exact defect size that caused the failure and the maximum stress attained during the experiments. The focused ion beam (FIB) opens revolutionary opportunities for testing materials at the microlevel by selective removing/carving material and generating complex geometries suitable for testing [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the methodology entails a large experimental scatter owing to the uncertainty in the determination of the exact defect size that caused the failure and the maximum stress attained during the experiments. The focused ion beam (FIB) opens revolutionary opportunities for testing materials at the microlevel by selective removing/carving material and generating complex geometries suitable for testing [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the outer oxide layer fractures in an intercrystalline mode, which indicates that the grain boundaries contribute to lower strength. Mueller et al observed similar slight differences between two values of K Ic measured in alumina fibers and suggested that it could be because of the differences between transgranular and intergranular fracture [64]. Since the oxide layer is growing while exposed to flowing LBE, it is likely that small amounts of LBE migrate into the grain boundaries.…”
Section: Discussionmentioning
confidence: 66%
“…In Ref [37] microscopic chevron-notched cantilever specimens, with dimensions W and B from ≈2 to ≈5 m were produced by focused ion beam milling in fused quartz and nanocrystalline alumina (grain size ≈60 nm). Testing was conducted under load-control, at room temperature and 20-50% relative humidity using a nanoindentation instrument at loading rates ≈2 N/s.…”
Section: Applicationmentioning
confidence: 99%